PREVALENCE OF SCHISTOSOMIASIS AMONG SCHOOL CHILDREN IN BAHRI LOCALITY, SUDAN - Elsammani, Nadia A; Ali Adam, Abdelghaffar; Mater, Adam Abdalla; Elamin, Mohamed Osman (International Journal of Research -GRANTHAALAYAH, 2019)
Schistosomiasis is a neglected tropical disease caused by blood flukes (trematode worms) the genus Schistosoma. Schistosomiasis is a chronic, debilitating disease that affects the populations of tropical and subtropical countries, especially children at School-age. In Sudan schistosomiasis is a major health problem adversely affecting the health of vulnerable populations. A cross-sectional study was conducted to determine the prevalence of schistosomiasis among school children in selected basic schools in Bahary Locality, Khartoum State, Sudan from December 2017 to January 2018. Urine and faecal samples were collected from 600 school-aged children and examined for the eggs of S. haematobium and S. mansoni using standard sedimentation and Kato technique, respectively. The overall of prevalence schistosomiasis 16,5% which the prevalence of S. haematobium among pupils examined was 16% and the prevalence of S. mansoni was 0.5%. Additionally, male’s reported higher prevalence (22.7%) of S. haematobium than the female’s (4.1%) also males reported higher prevalence of S. mansoni female with prevalence rate 7.7% and 2.2% for males and females respectively. According to the study participant age-groups; age group 13-15 years had the highest prevalence (22%) of S. haematobium was recorded and age group 10- 12 years comes next (18.5%) followed by age group 6 -9 years (7.5%); this difference of the age group as a factor was statistically significant (x2 = 17.9 –p value n =0.0) , but in S. mansoni age group 10-12 years had the highest (0.8%) prevalence , also there was statistically significant (P=0.04). This study highlights that schistosomiasis is a public health problem among children in Bahary locality. The findings of the study suggested appropriate intervention against schistosomiasis such as mass treatment, health education and control of the intermediate snail host.